Effects of different consolidation periods on bone formation and implant success in alveolar distraction osteogenesis: A clinical study - (:unkn) unknown (CHURCHILL LIVINGSTONE, 2013)
Purpose: The aims of this study were to compare the consolidation periods in alveolar distraction osteogenesis and evaluate the effects of this condition on bone formation, bone relapse and implant success in reconstruction of resorbed edentulous mandibles. Patients and methods: Eighteen patients were underwent vertical alveolar distraction osteogenesis under the same distraction protocol, except for variations in consolidation time. After a consolidation period of 5 weeks for Group 1 and 14 weeks for Group 2, 36 implants were placed to support their dentures. Bone height and relapse were evaluated using digital orthopantomographic radiographs. Results: The radiological findings showed that the mean distraction was 6.968 mm in Group 1 and 7.031 mm in Group 2. At the end of the consolidation period, the mean bone relapse was 0.832 +/- 0.135 mm in Group I and 0.738 +/- 0.135 mm in Group 2. At the end of 6 months, the mean bone relapse was 1.380 +/- 0.144 mm in Group 1 and 1.112 +/- 0.144 mm in Group 2. No significant difference existed between the two groups at any time. Conclusion: Consolidation periods may be reduced in alveolar distraction osteogenesis to enable more patient comfort by providing dentures early. (C) 2012 European Association for Cranio-Maxillo-Facial Surgery. Published by Elsevier Ltd. All rights reserved.
Keywords: Alveolar distraction osteogenesis; Consolidation period; Implant; Resorbed mandible; DEFICIENT EDENTULOUS RIDGES; ENDOSSEOUS IMPLANTS; OVERCORRECTION; RELAPSE; GRAFTS; HUMANS